PENDIDIKAN KEAGAMAAN DALAM MAKAM ULAMA (STUDI KASUS MAKAM MBAH DIMYATHI DESA SIDOREJO) - nafisah, nur; Amalia, Faidatul; Hidayatullah, Ahmad (Jurnal Kajian Manajemen Dakwah, 2022)
The kyai's grave is believed to be a medium that connects humans with God by means of pilgrimage or pilgrimage and is a place for people to deepen their religious knowledge with the existence of Islamic boarding schools and religious activities in it such as reciting routine prayers at graves, and so on. This study aims to describe the religious education contained in the tomb of mbah Dimyathi Kedawung, Comal. The method in this study is a qualitative method and the data obtained is presented descriptively. In obtaining the data needed by the author, namely by observation, interviews, and documentation. The data sources used in this study are primary data from interviews with Dimyathi's grandson and secondary data from grave documentation and Islamic boarding schools. The results showed that at Mbah Dimyathi's grave, various kinds of religious education had been carried out, such as Islamic boarding schools, reciting routines, khoul, places of pilgrimage.